Digital Augmented Reality (AR) Tahsin Development of Makharijul-Huruf Learning - Nelvawita Nelvawita; Idria Maita; Mochammad Novendri S (AJIS: Academic Journal of Islamic Studies, 2023)
The activity of reading the Al-Qur’an is an important lesson that must be understood by every Muslim because it is a guide in life and is of value in worship. The process of learning to read the Al-Qur’an is currently often ignored because it is covered by technological dynamics and is considered not too important with Latin readings. So this study is intended to present products in media development in learning makharijul than al-Qur'an letters with the Tahsin Digital Augmented Reality android application platform. This research goes through the stages of conducting research with the type of R&D and the Borg and Gall model. After going through several processions, it can be found in the results of this study that the media developed in the procession of learning makharijul letters in this Augmented Reality digital tahsin application can be accessed on the Play Store on the Android platform. Based on comments from experts, namely tahsin experts and experts in the field of technology, it has been shown that this application can be categorized as very valid and can be used in supporting the learning of makharijul letters, because of Augmented Reality technology which is unique in the delivery of each letter, then also equipped with animations and audio samples from scientifically verified experts. The Tahsin Digital Augmented Reality application can be used by anyone from basic education to higher education.